(untitled) (Journal of Hama University, 2022)
This study was conducted with the aim of knowing the effect of treatment with GnRH hormone when injected on the day (6 , 12 or on days 6 and 12) after artificial insemination in dairy cows on the pregnancy rate. The study included 40 cows divided randomly into 4 groups, each group included 10 of cows. The first group G1 (n = 10) was treated with Buserelin Acetate (Receptal ®), a synthetic derivative of GnRH hormone (10.5 μg/cow) on day 6 after artificial insemination, while the second group G2 (n = 10) was injected with the same treatment on day 12 after artificial insemination, while the third group G3 injected the same treatment on days 6 and 12 after artificial insemination, and the fourth group G4 (n=10) (the control group) injected with the physiological solution on days 6 and 12 after artificial insemination. The Pregnancy in cows was diagnosed using ultrasound on day 35 after insemination and by rectal palpation on day 90. The results showed a significant difference (P<0.05) in the pregnancy rate in groups G1, G2 and G3 when compared with the control group G4, and the results also show an increased risk of pregnancy loss between day 35 and day 90 after artificial insemination in the control group G4 when compared with groups that It was treated with hormonal treatment, as the results of the pregnancy test on the 90th day after treatment showed significant differences in the percentage of pregnancy (P < 0.05) in groups G1, G2 and G3 when compared with the control group G4. It can be concluded from this study that the use of treatment with GnRH hormone on days 6 and day 12 After artificial insemination, the rate of pregnancy can be improved and maintained, as the GnRH hormone works to support the work of the corpus luteum and increase its growth and development, and thus protect against fetal death resulting from a deficiency in the function of the corpus luteum.